ANALISIS ISI PADA ARTIKEL ROMANSA DI ZETIZEN.COM (STUDI ANALISIS ISI ARTIKEL ROMANSA PADA WEB ZETIZEN PERIODE 1 OKTOBER-30 NOVEMBER 2016) - Mawarni, Astrid Dian; Kusbandrijo, Bambang; Putri, Sukma Ari Ragil (Universitas 17 Agustus 1945 Surabaya, 2017)
The development of information is currently very rapid with the internet. Mass media such asnewspapers have now done a lot of rebranding to online media or websites. Just like what has beendone by jawapos newspaper which now has an online newspaper or commonly called with onlinemedia. In jawapos there is a zetizen rubric that used to be called detection. Zetizen discusses youngpeople one of them contained romance articles. This study chose the romance article because it is oneof the articles favored by teenagers today. The formulation of the problem of this research is how theconcept of romance in the articles displayed on the website zetizen.com? This study aims to find theconcept of romance and describe the message content of the romance article on zetizen.com. Themethod used to reveal it is by content analysis, that is using an approach with framing analysis. Theresults showed that the concept of romance that carried by zetizen that is in the form of new thingsthat are popular among teenagers. Here the author not only contains the words of romanticism thatmake teenagers fascinated with their partner but create a new concept of romance that slightlychanges the perception of adolescentsKeywords : Analysis, Content, Articles, Website, Zetizen.com